Pharmacoeconomic evaluation of weight-based vs fixed-dose pembrolizumab for non-small cell lung cancer in China - Wu, Meiyu; Yi, Yangke; Li, Andong; Meng, Kehui; Zhang, Zixuan; Shi, Chaohao; Tan, Chongqing; Wan, Xiaomin; Ma, Jinan (Frontiers in Immunology, 2025)
BackgroundWhile the immune checkpoint inhibitor pembrolizumab has improved outcomes for non-small cell lung cancer (NSCLC), the leading cause of cancer death in China, its standard fixed-dose regimen is costly. Given that studies demonstrate comparable efficacy between fixed and weight-based dosing, we aimed to compare the economic impact of these two dosing regimens in China.MethodsWe conducted a one-year budget impact analysis from the Chinese payer perspective comparing fixed-dose (200 mg Q3W) versus weight-based (2 mg/kg Q3W) pembrolizumab regimens. Model parameters, including lung cancer epidemiology, treatment costs and market penetration rates, were derived from published studies and open-access databases. Scenarios with and without institutional vial dose-sharing were analyzed, and comprehensive one-way and probabilistic sensitivity analyses (PSA) were performed to assess model robustness.ResultsThe standard fixed-dose regimen was projected to have an annual cost of $6.67 billion. In a dose-sharing scenario, the weight-based regimen reduced annual drug consumption by 34.41%, resulting in a total saving of $2.29 billion. This lowered the annual cost per patient from $86,392 to $56,661. Without dose-sharing, the weight-based regimen still yielded an annual saving of $76.93 million. PSA confirmed the robustness of these findings, showing a 50% probability of achieving savings greater than $2.09 billion in the dose-sharing scenario.ConclusionAdopting a weight-based dosing strategy for pembrolizumab, especially when optimized with vial-sharing protocols, offers substantial and achievable annual cost savings for the Chinese healthcare system without compromising therapeutic efficacy. Therefore, this regimen should be considered as a potential first-line treatment option for patients with advanced NSCLC.